Preparation method of metal bipolar plate coating of PEMFC and metal bipolar plate prepared by preparation method
The metal graphite composite coating is prepared on the metal bipolar plate of PEMFC through atmospheric plasma thermal spraying technology, which solves the corrosion problem of the metal bipolar plate in acidic environment, achieves excellent corrosion resistance and conductive properties, extends the battery life and Reduced costs.
Patent Information
- Application Number
- CN202411447211.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
Metal bipolar plates are prone to corrosion in the acidic environment of PEMFC, resulting in ionic contamination and passivation film formation, reducing performance and life. At the same time, the existing coating preparation methods have problems such as complex equipment, high cost or insufficient binding force.
Adopt the atmospheric plasma heat spraying technology, prepare metal graphite composite coating on the metal bipolar plate, and melts and cools the metal powder and graphite composite materials at high temperatures to form coatings with excellent corrosion resistance and conductive performance.
It achieves efficient anti-corrosion and improved conductivity of metal bipolar plates, extending the service life of the battery and reducing production costs.
Smart Images

Figure CN119361737A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bipolar plates, and in particular to a method for preparing a metal bipolar plate coating of a PEMFC and a prepared metal bipolar plate. Background Art
[0002] In proton exchange membrane fuel cells (PEMFCs), bipolar plates, as one of the key components, are crucial to the weight and cost control of the battery. At present, bipolar plates are mainly classified into graphite bipolar plates, composite bipolar plates and metal bipolar plates according to materials. Graphite bipolar plates have good conductivity and stability, but face challenges such as complex manufacturing, poor sealing and excessive weight. Composite bipolar plates have more balanced performance, but the manufacturing cost is higher. In contrast, metal bipolar plates are widely used for their cost-effectiveness, excellent airtightness and easy processing. Common metal bipolar plate materials include stainless steel, aluminum alloy, titanium and titanium alloy.
[0003] However, metal bipolar plates are susceptible to corrosion and dissolution in the acidic environment inside PEMFCs, and the leached ions may contaminate the proton exchange membrane and catalyst layer, seriously reducing performance and life. In addition, a passivation film will be generated. Although the passivation film can improve the corrosion resistance of the metal to a certain extent, its electrical conductivity is poor, which will cause a significant increase in the contact resistance between the bipolar plate and the battery diffusion layer, reducing the output power.
[0004] To solve the corrosion and passivation problems of metal bipolar plates, applying corrosion-resistant conductive coatings has become a simpler and more effective strategy.
[0005] Among the existing methods for preparing metal bipolar plate coatings, chemical vapor deposition and physical vapor deposition have complex equipment and high costs; electroplating has low costs and simple processes, but the bonding between the coating and the substrate is weak; the chemical plating method does not require power and is simple to operate, but the stability of the plating solution is difficult to control.
[0006] Atmospheric plasma thermal spraying (APS) is a mature, fast, economical and environmentally friendly process. A plasma arc driven by direct current is used as a heat source to heat the required spraying material to a molten or semi-molten state, and then sprayed on the substrate surface to form a coating to achieve the purpose of corrosion protection. Graphite has good corrosion resistance and conductivity, and is suitable as a metal bipolar plate coating material. However, graphite has a high melting point, and existing technologies cannot directly prepare graphite into metal bipolar plate coatings through atmospheric plasma thermal spraying technology.
[0007] Therefore, the present invention adopts atmospheric plasma thermal spraying technology to prepare a metal-graphite composite coating with excellent corrosion resistance and electrical conductivity on a metal bipolar plate. Summary of the invention
[0008] In order to solve the problem that the existing technology cannot directly prepare graphite into metal bipolar plate coatings through atmospheric plasma thermal spraying technology, the present invention adopts atmospheric plasma thermal spraying technology to provide a method for preparing metal bipolar plate coatings for PEMFC with excellent corrosion resistance and conductivity.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides a method for preparing a metal bipolar plate coating of a PEMFC, and the technical scheme thereof is as follows: Pretreatment of the coating powder material: drying the composite material of metal powder coated with graphite, wherein the mass ratio of the metal powder to the graphite in the composite material is 50-90:10-50; Substrate pretreatment: After cutting, grinding, polishing, cleaning and drying the substrate, the substrate surface is sandblasted; Atmospheric plasma thermal spraying: Fix the pretreated substrate in the working area so that the direction of the spray gun and the substrate are perpendicular to each other, and then write a positioning program according to the size of the substrate and the clamping position; load the pretreated coating powder material into the powder feeding device, set the spraying parameters and start spraying until the coating reaches a certain thickness.
[0010] Preferably, the metal powder is copper powder or nickel powder.
[0011] Preferably, in the coating powder material pretreatment step, the metal powder and graphite are dried at a temperature of 90-100° C. and for a time of 15-25 min, in order to facilitate powder feeding by the spraying equipment after the powder is dried.
[0012] Preferably, in the substrate pretreatment step, the polishing step uses sandpaper to polish the substrate, the purpose of which is to polish away oil stains and pits on the surface of the substrate.
[0013] Specifically, the substrate was polished using 800-mesh, 1000-mesh and 2500-mesh sandpapers in order of roughness.
[0014] Preferably, the polishing step uses a polishing cloth and a polishing paste to polish the surface of the substrate. Further make the surface of the substrate smooth and flat.
[0015] More preferably, the polishing paste has a mesh size of 2000-3000.
[0016] Preferably, the cleaning step first uses distilled water for the first cleaning, and then uses anhydrous Wash a second time with ethanol.
[0017] Preferably, in the substrate pretreatment step, the sandblasting uses a sandblasting machine to spray sand particles or abrasives onto the substrate surface at high speed and in a directional manner through a high-speed airflow. The purpose is to roughen the surface through the scouring and cutting action of the abrasive, thereby increasing the contact area between the substrate surface and the coating and facilitating the adhesion of the coating.
[0018] Preferably, the substrate is one of a stainless steel bipolar plate, an aluminum alloy bipolar plate and a titanium metal bipolar plate.
[0019] More preferably, the substrate is a titanium metal bipolar plate.
[0020] Preferably, in the atmospheric plasma thermal spraying step, the spraying parameters are set to a voltage of 45-55V, a current of 300-900A, and a powder feeding speed of 25-35g / min.
[0021] More preferably, the voltage is 50V, the current is 650A, and the powder feeding speed is 30g / min.
[0022] Preferably, in the atmospheric plasma thermal spraying step, the spraying parameters are set to argon flow rate of 20-70 L / min, hydrogen flow rate of 0.5-3 L / min, and nitrogen flow rate of 1-10 L / min.
[0023] More preferably, the flow rate of argon is 45 L / min, hydrogen is 1 L / min, and nitrogen is 5 L / min.
[0024] Preferably, the coating has a thickness of 25-35 μm and is uniform.
[0025] Specifically, the optimal thickness range of the coating is 25 to 35 μm. If the coating is too thin, it may not provide sufficient protection, making the metal bipolar plate susceptible to corrosion, affecting the conductivity and durability of the battery; if the coating is too thick, it may increase the contact resistance of the battery, reduce the output power and efficiency of the battery, and increase the cost.
[0026] More preferably, the coating has a thickness of 30 μm.
[0027] Compared with the prior art, the present invention provides a method for preparing a metal bipolar plate coating for PEMFC, which adopts atmospheric plasma thermal spraying technology, overcomes the defect that graphite has a high melting point and is difficult to be directly prepared into a coating by atmospheric plasma thermal spraying technology. Metal powder is melted into a molten state at a high temperature, and the molten metal is wrapped with graphite and contacts and collides with a substrate under the action of a high-speed airflow and then cooled and formed, thereby achieving the purpose of preparing graphite on the metal bipolar plate to form a coating. The prepared metal bipolar plate coating for PEMFC has excellent corrosion resistance and electrical conductivity.
[0028] The present invention also provides a metal bipolar plate of PEMFC, the surface of which is sprayed with the metal bipolar plate coating of PEMFC as described above, and the beneficial effects thereof are as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 SEM electron microscope images of nickel-coated graphite and copper-coated graphite coatings provided by the present invention; Figure 2 XRD spectra of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention; Figure 3 The XPS diffraction pattern of the nickel-coated graphite coating provided by the present invention; Figure 4 The XPS diffraction pattern of the copper-clad graphite coating provided by the present invention; Figure 5 Potentiodynamic polarization curves of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention; Figure 6 Constant potential polarization curves of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention; Figure 7 Curves showing changes in interface contact resistance of nickel-coated graphite and copper-coated graphite coatings with different mass ratios as a function of pressure provided by the present invention; Figure 8 Curves showing changes in interface contact resistance of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention after constant potential cathode polarization as a function of pressing force; Fig. 9 A schematic diagram of a method for measuring the contact resistance between a test sample and carbon paper provided by the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the description of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0033] In order to demonstrate that the method for preparing a metal bipolar plate coating for PEMFC provided by the present invention has outstanding technical effects compared with the prior art, the present invention will be described in conjunction with the following embodiments and comparative examples to illustrate the beneficial effects of the present invention.
[0034] Example 1 Pretreatment of coating powder material: nickel-coated graphite powder containing 90% nickel powder and 10% graphite is heated to 100°C in a powder dryer and maintained at this temperature for 20 min to remove water so that the coating material remains dry; Substrate pretreatment: (1) Use a metal cutting machine to cut the substrate into a size of 50mm*50mm*2mm for subsequent processing; (2) Use 800 mesh, 1000 mesh and 2500 mesh sandpaper to grind the substrate; (3) Use a polishing cloth with 3000 mesh polishing paste to polish the surface of the substrate; (4) Use distilled water to clean the substrate, then place the substrate in anhydrous ethanol for cleaning, and dry it at room temperature (5) Use a sandblasting machine to sandblast the surface of the substrate. The power used for sandblasting is compressed air, which uses high-speed airflow to spray sand or abrasives onto the surface of the substrate at high speed.
[0035] The substrate is a titanium metal bipolar plate.
[0036] Atmospheric plasma thermal spraying: Fix the pretreated substrate in the working area so that the direction of the spray gun and the substrate are perpendicular to each other, and then write a positioning program according to the size of the substrate and the clamping position; load the pretreated coating powder material into the powder feeding device, set the spraying parameters and start spraying until the coating reaches a certain thickness.
[0037] The spraying parameters are: voltage 50V, current 650A, argon flow rate 45L / min, hydrogen flow rate 1L / min, nitrogen flow rate 5L / min, and powder feeding speed 30g / min.
[0038] Example 2 The nickel-coated graphite powder containing 90% nickel powder and 10% graphite in Example 1 was replaced with nickel-coated graphite powder containing 75% nickel powder and 25% graphite, and the remaining steps and operations were the same as in Example 1.
[0039] Example 3 The nickel-coated graphite powder containing 90% nickel powder and 10% graphite in Example 1 was replaced with nickel-coated graphite powder containing 50% nickel powder and 50% graphite, and the remaining steps and operations were the same as in Example 1.
[0040] Example 4 The nickel-coated graphite powder containing 90% nickel powder and 10% graphite in Example 1 was replaced by copper-coated graphite powder containing 90% copper powder and 10% graphite, and the remaining steps and operations were the same as in Example 1.
[0041] Example 5 The nickel-coated graphite powder containing 75% nickel powder and 25% graphite in Example 2 was replaced by copper-coated graphite powder containing 75% copper powder and 25% graphite, and the remaining steps and operations were the same as in Example 1.
[0042] Example 6 The nickel-coated graphite powder containing 50% nickel powder and 50% graphite in Example 3 was replaced by copper-coated graphite powder containing 50% copper powder and 50% graphite, and the remaining steps and operations were the same as those in Example 1.
[0043] The coatings prepared in Examples 1-6 were tested for performance, and the test method was as follows: Microscopic morphology test: The microstructure of the coating was analyzed by scanning electron microscopy using a ZEISS Sigma 500 instrument.
[0044] Phase composition XRD spectrum analysis: The coating phase composition was analyzed by X-ray diffraction analysis using Shimadzu AXIS SUPRA+ equipment.
[0045] XPS diffraction pattern analysis of phase composition: The crystal structure of the coating was characterized by Rigaku Smartlab 3 KW X-ray diffractometer.
[0046] Corrosion resistance test: The CHI760E three-electrode electrochemical workstation was used to perform potentiodynamic polarization and constant potential polarization experiments on the substrate covered with the coating prepared by APS to determine the corrosion resistance of the coating. The sample was used as the working electrode (WE), the platinum sheet was used as the counter electrode (CE), and the silver chloride electrode was used as the reference electrode (RE). The electrochemical experiment simulated the working environment of the PEMFC cathode, in which the solution temperature was 25°C, air was blown in, and the solution ratio was 0.5 mol / L H 2 SO 4 and HF with a mass fraction of 0.002‰. Use 80ml of the prepared solution at a time. Grind the material to remove burrs, embed it with epoxy resin, and only expose the coating surface with an exposed area of 1CM 2 The effects of different mass ratios of coating materials on coating performance in Examples 1-6 were analyzed.
[0047] Before each test, the samples were stabilized at open circuit potential (OCP) for 60 min. −1 Rate scan. In the constant potential polarization experiment, the potential was set at 0.6 V and air was introduced into the corrosion solution to simulate the cathode environment for 5 hours.
[0048] Contact resistance test: The contact resistance of the coating before and after the constant potential polarization experiment was tested to explore the conductive properties of the coating before and after corrosion. The schematic diagram of the contact resistance measurement between the test sample and the carbon paper is as follows: Fig. 9 As shown. Use a press to apply pressure to both ends of the structure shown in the figure, and monitor and adjust the pressure value through the press control end. The DC low resistance tester model used is American RK2511BL, and the applied pressure range is 20-300N / cm 2 , the pressure gradient is 20 N / cm 2 .
[0049] The following is the theoretical calculation process of the interface contact resistance test.
[0050] Fig. 9 In (a), taking copper as an example, the total resistance of the test system is R 1 , Copper block resistor R Cu , R C is the carbon paper resistor, R Cu / C is the contact resistance between the copper block and the carbon paper, and the volume resistance of the bipolar plate is R P, the interface contact resistance between the plate coating surface and the carbon paper is ICR , the contact area between the copper block, sample and carbon paper is S .
[0051] but R 1 =2(R Cu +R C +R Cu / C +ICR) +R P Then change the device to Fig. 9 (b) The test method is the same as above. The overall resistance value measured at this time R2 for: R 2 =2 (R Cu +R Cu / C )+ R C Since the volume resistance of carbon paper and sample is very small compared with the contact resistance, the volume resistance of carbon paper is ignored. R C , the bulk resistance of the sample R P , then: (R 1 -R 2 )S / 2=ICR The coatings prepared in the above Examples 1-6 were subjected to performance tests, with titanium metal bipolar plates as the control group. The test results are as follows: Microscopic morphology test: Figure 1 These are SEM images of nickel-coated graphite and copper-coated graphite coatings.
[0052] like Figure 1 As shown, (a) is a nickel-coated graphite coating, (b) is a copper-coated graphite coating, the bottom is a titanium substrate, and the upper middle part is the coating. Figure 1 It can be observed that the average thickness of the prepared coating is about 30 microns, and the coating is closely bonded to the substrate surface.
[0053] Phase composition XRD spectrum analysis: Figure 2 XRD spectra of nickel-coated graphite and copper-coated graphite coatings with different mass ratios.
[0054] Figure 2 (a) is the phase analysis corresponding to the nickel-coated graphite coating, such as Figure 2As shown in (a), the XRD spectra of coatings with different mass ratios all show characteristic diffraction peaks of graphite with (002) crystal plane and characteristic peaks of nickel with (111), (200) and (220) crystal planes. It can be observed that with the increase of graphite content in the coating material, the intensity of graphite diffraction peak increases, and the intensity of corresponding characteristic peak of nickel decreases. At the same time, NiO phase is also generated. This is because the metal nickel is partially oxidized to form NiO, including rapid oxidation under high temperature plasma flame flow and slow oxidation in air environment after preparation. Its formation process can be explained by the oxidation equation of nickel: 2Ni+O2→2NiO.
[0055] Figure 2 (b) is the phase analysis corresponding to the copper-clad graphite coating, such as Figure 2 As shown in (b), the situation is similar to that of nickel coating. After spraying, copper and graphite phases still exist. As the graphite content in the coating material increases, the intensity of the graphite diffraction peak increases, and the intensity of the corresponding characteristic peak of copper decreases. At the same time, the CuO phase is also generated. This is because the metal copper is partially oxidized to form CuO, and the oxidation reason is the same as above. Its formation process can be explained by the oxidation equation of copper: 2Cu+O2→2CuO.
[0056] XPS diffraction pattern analysis of phase composition: Figure 3 The XPS diffraction pattern of the nickel-coated graphite coating provided by the present invention.
[0057] Figure 3 (a) is the full spectrum obtained after a full scan of the nickel coating. The figure shows that the main elements on the surface of the composite coating are C, O and Ni, among which C and Ni elements come from the nickel coating powder, and O element mainly comes from the atmospheric environment.
[0058] Figure 3 (b) is the photoelectron spectrum of C1s, in which the OCO bond is located at 287.7 eV; the C-bond is located at 286.1 eV, the CC bond of the sp2 orbital is located at 284.9 eV; the graphite is located at 284.1 eV; this indicates that the graphite in the coating mainly exists in the form of graphite monomers and CC bonds, and the presence of CO and OCO bonds indicates that part of the graphite is partially oxidized during the spraying process.
[0059] Figure 3 (c) is the photoelectron spectrum of O1s. The O element is mainly composed of Ti-OC bonds and Ti-OH bonds, indicating that the oxygen element in the coating mainly comes from the oxidation of the substrate and the coating material.
[0060] Figure 3 (d) Ni 2 XPS spectrum of Ni element is mainly Ni 3+、Ni 2+ This is related to the different degrees of oxidation of the Ni element in the original powder material when it passes through the high temperature of the APS process.
[0061] Figure 4 The XPS diffraction pattern of the copper-clad graphite coating provided by the present invention.
[0062] Figure 4 (a) is the full spectrum obtained after the full scan of the copper clad coating. The figure shows that the main elements on the surface of the composite coating are C, O and Cu, of which C and Cu come from the copper clad coating powder, and O mainly comes from the atmosphere. Similarly, a narrow area scan analysis is performed on each element. Figure 4 (b), (c), and (d) are the photoelectron spectra of C1s, the photoelectron spectrum of O1s, and the XPS spectrum of Cu2, respectively. Similar to the nickel coating, graphite and copper were partially oxidized during the spraying process.
[0063] Corrosion resistance test: Figure 5 The potentiodynamic polarization curves of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention are shown.
[0064] like Figure 5 As shown, the corrosion current density of the coatings of Examples 1-6 with different mass ratios is significantly reduced compared to the bare titanium plate, indicating that the coating effectively improves the corrosion resistance. The corrosion current density of the nickel-coated graphite coating decreases with the increase of the mass proportion of graphite in the coating powder material, and the corrosion potential is basically the same. The corrosion current density of the copper-coated graphite coating also decreases with the increase of the mass proportion of graphite in the coating powder material, and the corrosion potential also shows a downward trend with the increase of the mass proportion of graphite in the coating powder material. It shows that the mass proportion of graphite in the coating powder material affects the corrosion performance of the coating in the potentiodynamic polarization experiment, showing a trend that the corrosion current density decreases with the increase of the mass proportion of graphite. The decrease in corrosion current density reflects the improvement of corrosion resistance.
[0065] Figure 6 The constant potential polarization curves of nickel-coated graphite and copper-coated graphite coatings with different mass ratios provided by the present invention are shown.
[0066] from Figure 6 It can be seen that as the test time increases, the corrosion current density decreases rapidly and then gradually stabilizes, which is attributed to the formation of a surface passivation layer. The corrosion current density of the coatings of Examples 1-6 with different mass ratios is significantly reduced compared to that of the bare titanium plate when stable, and the corrosion current density decreases by about one order of magnitude, indicating that the titanium plate covered with the coating can still maintain better corrosion resistance and stability after a long period of corrosion compared to the bare titanium plate.
[0067] Contact resistance test: Figure 7 Curves showing changes in interface contact resistance of nickel-coated graphite and copper-coated graphite coatings with different mass ratios as a function of pressure provided by the present invention; Figure 8 The present invention provides a curve of the interface contact resistance of nickel-coated graphite and copper-coated graphite coatings with different mass ratios after constant potential cathode polarization as the pressing force changes.
[0068] from Figure 7 and Figure 8 It can be seen that the interface contact resistance of the coating before and after corrosion has a significant downward trend with the increase of pressure. When the pressure value of the contact interface is greater than 100N·cm -2 The interface contact resistance value will remain constant. Usually the PEMFC stack assembly value is about 140N·cm -2 about.
[0069] Table 1 shows the trend of interfacial contact resistance with the mass percentage of graphite in the coating material.
[0070] As shown in Table 1, at 140 N·cm -2 Under the pressure of , the interfacial contact resistance shows a downward trend with the increase of the mass proportion of graphite in the coating material, which indicates that the increase of graphite content helps to improve the conductivity of the coating. After the constant potential test, the contact resistance of each coating increased to varying degrees, but the downward trend of the contact resistance with the increase of the mass proportion of graphite in the coating did not change.
[0071] Table 1 Trend of interfacial contact resistance with the mass percentage of graphite in coating materials Samples <![CDATA[Before polarization (mΩ*cm -2 )]]> <![CDATA[After polarization(mΩ*cm -2 )]]> Ni:G=90:10 30.3 47.5 Ni:G=75:25 29.3 42.9 Ni:G=50:50 25.2 38.9 Cu:G=90:10 24.3 26.5 Cu:G=75:25 20.5 24.4 Cu:G=50:50 17.4 21.2 Note: ICR at 1.4 MPa before and after polarization. In summary, the method for preparing the metal bipolar plate coating of PEMFC provided by the present invention melts the metal powder into a molten state at a high temperature, and the molten metal is wrapped with graphite and contacts and collides with the substrate under the action of high-speed airflow, and then cooled and formed, so as to achieve the purpose of preparing graphite to form a coating on the metal bipolar plate, and adopts the atmospheric plasma thermal spraying technology to overcome the defect that the melting point of graphite is high and it is difficult to prepare the coating directly by the atmospheric plasma thermal spraying technology. The prepared metal bipolar plate coating of PEMFC has excellent corrosion resistance and electrical conductivity, and can still maintain good corrosion resistance and stability after a long period of corrosion.
[0072] Although the terms such as metal bipolar plate, PEMFC and atmospheric plasma thermal spraying are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a metal bipolar plate coating for PEMFC, characterized in that: Pretreatment of the coating powder material: drying the composite material of metal powder coated with graphite, wherein the mass ratio of the metal powder to the graphite in the composite material is 50-90:10-50; Substrate pretreatment: After cutting, grinding, polishing, cleaning and drying the substrate, the substrate surface is sandblasted; Atmospheric plasma thermal spraying: Fix the pretreated substrate in the working area so that the direction of the spray gun and the substrate are perpendicular to each other, and then write a positioning program according to the size of the substrate and the clamping position; load the pretreated coating powder material into the powder feeding device, and start spraying after setting the spraying parameters until the spraying is completed.
2. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: The metal powder is copper powder or nickel powder.
3. The method for preparing the metal bipolar plate coating of PEMFC according to claim 1, characterized in that: In the coating powder material pretreatment step, the metal powder and graphite are dried at a temperature of 90-100° C. and for a drying time of 15-25 minutes.
4. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: In the substrate pretreatment step, the grinding step uses sandpaper to grind the substrate; the polishing step uses a polishing cloth and a polishing paste to polish the surface of the substrate; the cleaning step first uses distilled water for the first cleaning, and then uses anhydrous ethanol for the second cleaning.
5. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: In the substrate pretreatment step, the sandblasting uses a sandblasting machine to spray sand particles or abrasives onto the surface of the substrate in a high-speed and directional manner through a high-speed airflow.
6. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: The substrate is one of a stainless steel bipolar plate, an aluminum alloy bipolar plate and a titanium metal bipolar plate.
7. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: In the atmospheric plasma thermal spraying step, the spraying parameters are set as a voltage of 45-55V, a current of 300-900A, and a powder feeding speed of 25-35g / min.
8. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: In the atmospheric plasma thermal spraying step, the spraying parameters are set to argon flow rate of 20-70 L / min, hydrogen flow rate of 0.5-3 L / min, and nitrogen flow rate of 1-10 L / min.
9. The method for preparing a metal bipolar plate coating for PEMFC according to claim 1, characterized in that: The coating has a thickness of 25-35 μm and is uniform.
10. A metal bipolar plate for PEMFC, characterized in that: A metal bipolar plate coating for PEMFC according to claims 1 to 9 is sprayed on its surface.